Future scenarios for applying artificial intelligence techniques at the Training Department at A Saudi government university - Al-Harbi, Dalia Abdulaziz; Al-Luhidan, Maryam Abdullah; Mohammed, Salwa Abdo; Al-Kathiri, Jamilah Faisal; Al-Tuwaijri, Fatima Abdulaziz (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the reality of applying artificial intelligence techniques and the requirements for their implementation, as well as to build proposed future scenarios. The researcher used a descriptive approach and future studies methodology, conducting interviews with 7 heads of training units and distributing 10 questions to 11 employees from the training department at Imam Muhammad bin Saud Islamic University. The results showed that the use of artificial intelligence applications is limited and needs development, and that training employees on these techniques will improve performance and efficiency. The study also emphasized the importance of administrative leadership support for digital transformation and the provision of necessary resources. The researchers recommended that the human resources and training management adopt a gradual strategic transformation based on an analysis of the university’s internal and external environment.